Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1074/mcp.m112.026583
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Chloroplast Ribonucleoprotein Complex Containing Trans-splicing Factors, Intron RNA, and Novel Components

Abstract: Maturation of chloroplast psaA pre-mRNA from the green alga Chlamydomonas reinhardtii requires the trans-splicing of two split group II introns. Several nuclear-encoded trans-splicing factors are required for the correct processing of psaA mRNA. Among these is the recently identified Raa4 protein, which is involved in splicing of the tripartite intron 1 of the psaA precursor mRNA. Part of this tripartite group II intron is the chloroplast encoded tscA RNA, which is specifically bound by Raa4. Using Raa4 as bai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
45
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(45 citation statements)
references
References 64 publications
(46 reference statements)
0
45
0
Order By: Relevance
“…Recent results revealed that splicing of psaA-i1 and -i2 is assisted by at least two high molecular weight protein complexes (subcomplexes I and II) harboring the general splicing factor Raa1 together with intron-specific subunits (17,24). Here, we provide the first evidence for a high molecular weight apparatus involved in trans-splicing of the psaA mRNA, which is the first report of a high molecular weight splicing apparatus from a eukaryotic organelle.…”
mentioning
confidence: 52%
See 4 more Smart Citations
“…Recent results revealed that splicing of psaA-i1 and -i2 is assisted by at least two high molecular weight protein complexes (subcomplexes I and II) harboring the general splicing factor Raa1 together with intron-specific subunits (17,24). Here, we provide the first evidence for a high molecular weight apparatus involved in trans-splicing of the psaA mRNA, which is the first report of a high molecular weight splicing apparatus from a eukaryotic organelle.…”
mentioning
confidence: 52%
“…By using Raa4 as a bait, Rat2 was found among subcomplex I proteins (24). RT-PCR analysis, data from LC-MS analyses (24), and a new gene model prediction of the recent C. reinhardtii database version 5.5 led to an extension of the previously predicted size of the proposed gene product to about 144 kDa. A reevaluation of the gene annotation was conducted with mutant L135F, which is allelic to the previously described mutant TR72:75 (22) (supplemental Fig.…”
Section: Core Components Of Trans-splicing Subcomplexes I and Ii-mentioning
confidence: 99%
See 3 more Smart Citations